2012
DOI: 10.1002/adfm.201102171
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Electrospun Fibers for Cancer Therapy

Abstract: Iron oxide nanoparticles (IONPs) for magnetic hyperthermia in cancer treatment have recently gained substantial interest. Unfortunately, the use of free IONPs still faces major challenges such as poor tumor targetability, high variability in the amount of IONPs taken up by the tumor and the IONP leakage from dead cancer cells into the surrounding healthy tissues. The present work reports on electrospun fiber webs, heavily loaded with 50 nm sized IONPs. The high loading capacity of the fibers enables significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
59
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 45 publications
0
59
0
1
Order By: Relevance
“…Previous studies have suggested to use polymeric formulations to coat or encapsulate Fe 3 O 4 NPs when they are used in magnetic fluid hyperthermia application, due to their improved physiochemical properties and biocompatibility [15,16]. Recently, Huang et al [17] described the incorporation of IONPs into electrospun polystyrene fibers for the purpose of developing novel mediators for magnetic hyperthermia as an anti-cancer strategy. They suggested that the use of electrospun fibers for the encapsulation of IONPs has the additional advantage of fibers displaying a very high surface area over volume ratio, which may enhance their interactions with e.g., surrounding cells and the possible use of coated fibers for cell binding applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested to use polymeric formulations to coat or encapsulate Fe 3 O 4 NPs when they are used in magnetic fluid hyperthermia application, due to their improved physiochemical properties and biocompatibility [15,16]. Recently, Huang et al [17] described the incorporation of IONPs into electrospun polystyrene fibers for the purpose of developing novel mediators for magnetic hyperthermia as an anti-cancer strategy. They suggested that the use of electrospun fibers for the encapsulation of IONPs has the additional advantage of fibers displaying a very high surface area over volume ratio, which may enhance their interactions with e.g., surrounding cells and the possible use of coated fibers for cell binding applications.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these previous studies focused primarily on the production and characterization of magnetic fibers [18][19][20][21]. However, studies taking advantage of the potential of local heat-generating capability of magnetic electrospun nanofiber composites upon application of alternating magnetic field for hyperthermia treatment are limited [17,22]. One study reports on a magnetic nanofiber that encapsulated magnetite NPs being used for cancer therapy, which was delivered by surgical or endoscopic methods precisely to the tumor site.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] When these linear nanostructures are modifi ed further through the introduction of functional nanoparticles, they can be applied for photocatalysis, [ 21 ] and hyperthermia treatment in cancer therapy. [ 22 ] Desired properties of hybrid nanofi bers often include nanometric dimensions, versatile functionalization, and nanoparticles with homogeneous distribution. The most commonly employed methods include electrospinning, [ 23,24 ] template-assisted methods, [ 25,26 ] and cooperative self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the high porosity and interconnected porosity of nanofibers makes it easy for cell binding, thus reduced metastasis of cancer cells when used locally [10,11]. Various anticancer drugs, such as doxorubicin (DOX), paclitaxel (PTX) and dichloroacetate (DCA) have been successfully electrospun into fibers which showed enhanced anticancer efficacy [12][13][14].…”
Section: Introductionmentioning
confidence: 99%